The Relationship Between the Intensity of Smartphone Use and Sleep Quality in Class VIII Teenagers at SMPN 4 Genteng Banyuwangi - Fatimatuz Zahro; Susi Wahyuning Asih; Asmuji (Cleanliness: Journal of Health Sciences and Medical Research, 2024)
Using a smartphone before bed can make a person's sleep time late and not according to the time. When someone plays with a smartphone at night, the brain will think that this is not sleep time because of the blue light emitted by the smartphone. If the brain thinks that it is not hours of sleep, the duration of smartphone users' sleep will decrease and this will affect the quality of their sleep. Poor sleep quality in teenagers will affect all activities and in daily life. This research aims to determine the relationship between the intensity of smartphone use and sleep quality in teenagers. This research uses a correlational research design with a quantitative research model using a cross-sectional approach. The population in this study was class students with a sample of 112 people taken using simple random sampling techniques. The instrument used in this study used a likert scale questionnaire. Statistical test between smartphone usage intensity and sleep quality measured using Spearman Rank (rho) with α = 0.05.  This research shows there is a relationship between the intensity of smartphone use and sleep quality. The direction of a positive relationship with strength is sufficient, meaning that the greater the intensity of using a smartphone, the less good it will have an impact on poor sleep quality. Using a smartphone at night will cause the brain to receive external stimuli in the form of sound, light and vibrations from the smartphone, this causes a person to wake up at night and if it lasts a long time it will disrupt the quality of students' sleep. Discussion: Therefore, it is necessary to monitor smartphone use in students so that sleep quality is better.